2018
DOI: 10.1038/s41431-018-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

De novo repeat interruptions are associated with reduced somatic instability and mild or absent clinical features in myotonic dystrophy type 1

Abstract: Myotonic dystrophy type 1 (DM1) is a multisystem disorder, caused by expansion of a CTG trinucleotide repeat in the 3'-untranslated region of the DMPK gene. The repeat expansion is somatically unstable and tends to increase in length with time, contributing to disease progression. In some individuals, the repeat array is interrupted by variant repeats such as CCG and CGG, stabilising the expansion and often leading to milder symptoms. We have characterised three families, each including one person with variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 43 publications
6
100
0
Order By: Relevance
“…In the rest of intergenerational transmissions reported, and in the case of our patients P2 and P4, anticipation could not be assessed since patients in the next generation are still asymptomatic. The explanation for these findings is not apparent, since anticipation is not expected in these families; indeed, interruptions are thought to be related to a stabilization or even contraction of the pathological expansion (Braida et al, ; Cumming et al, ; Musova et al, ; Pešović et al, ; Tomé et al, ). However, anticipation was found in our studied intergenerational transmission, with this finding being also reported in other interrupted DM1 patients based on reported age of onset (Table ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the rest of intergenerational transmissions reported, and in the case of our patients P2 and P4, anticipation could not be assessed since patients in the next generation are still asymptomatic. The explanation for these findings is not apparent, since anticipation is not expected in these families; indeed, interruptions are thought to be related to a stabilization or even contraction of the pathological expansion (Braida et al, ; Cumming et al, ; Musova et al, ; Pešović et al, ; Tomé et al, ). However, anticipation was found in our studied intergenerational transmission, with this finding being also reported in other interrupted DM1 patients based on reported age of onset (Table ).…”
Section: Discussionmentioning
confidence: 93%
“…We detected the contraction of the expansion between patients P2 and P4, but expansion between patients P3 and P5. Previous studies suggest that CTG expansion containing variant repeat patterns display more frequently stable, or even contracted, DMPK alleles instead of further expanded DMPK alleles (Cumming et al, ; Musova et al, ; Pešović et al, ; Tomé et al, ). However, some studies have also found the expansion of the interrupted alleles from one generation to the other (Braida et al, ; Cumming et al, ; Pešović et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this mutational mechanism has previously been suggested in the origin of pure repetitive stretches of (CCG) n in the middle of the expanded (CTG) n , in DM1. The CCG interruptions may appear individually, in runs of CCGCTG or in a continuously block (Braida et al., ; Cumming et al., ; Pešović et al., ). The CCG blocks may be as large as 40 repeat units (Pešović et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that these large pure (ATTTT) n alleles with haplotype VIII have been originated by an (ATTTC) n deletion, because (1) ATTTC repeat contractions have never been detected in 22 parent-to-offspring transmissions (Corral-Juan et al, 2018;Seixas et al, 2017) and (2) Interestingly, this mutational mechanism has previously been suggested in the origin of pure repetitive stretches of (CCG) n in the middle of the expanded (CTG) n , in DM1. The CCG interruptions may appear individually, in runs of CCGCTG or in a continuously block (Braida et al, 2010;Cumming et al, 2018;Pešović et al, 2017). The CCG blocks may be as large as 40 repeat units (Pešović et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation